Relation of Red Cell Distribution Width With CHA2DS2-VASc Score in Patients With Nonvalvular Atrial Fibrillation. (October 2014) - Kurt, Mustafa; Tanboga, Ibrahim Halil; Buyukkaya, Eyup; Karakas, Mehmet Fatih; Akçay, Adnan Burak; Sen, Nihat
Background: Red cell distribution width (RDW) has been shown to be helpful in predicting adverse long-term events in patients with cardiovascular diseases. However, to date, no study has been conducted on the relationship between RDW and thromboembolism risk in atrial fibrillation (AF). Therefore, we aimed to investigate the relationship between RDW and CHA2DS2-VASc score used for the evaluation of thromboembolism risk in patients with AF. Methods: The study population consisted of 320 patients with AF. We calculated CHA2DS2-VASc risk score for each patient and baseline hemoglobin, white blood cell, RDW, mean platelet volume, platelet counts, estimated glomerular filtration rate (eGFR), left ventricular ejection fraction (LVEF), and left atrial volume index (LAVi) were measured. Results: High CHA2DS2-VASc score group had higher RDW, lower LVEF, higher LAVi, and lower eGFR values when compared to the low CHA2DS2-VASc score group. The multivariate logistic regression analysis performed to predict high CHA2DS2-VASc scores revealed that RDW eGFR, LVEF, and LAVi were independent predictors. The area under the receiver–operating characteristic curve of RDW was 0.65 (0.59-0.71, P < .001) to predict high CHA2DS2-VASc score. Conclusion: Our study results indicate that RDW values are significantly correlated with CHA2DS2-VASc score in nonanemic patients with AF, while also being independent predictor of high CHA2DS2-VASc score.